Drug use and antisocial behavior among adolescents attending public schools in Brazil - Nardi,Fernanda Lüdke (2012)
INTRODUCTION: Drug use is a social and a public health problem that has been related with antisocial behavior. The aim of this study was to evaluate the relationship between drug use and antisocial behavior among adolescents attending public schools in Brazil. METHOD: A total of 7,176 adolescents from low-income neighborhoods and public schools aged 14 to 19 years were assessed in five geographical regions in Brazil. Data on biosociodemographic characteristics and on drug use and antisocial behavior were assessed from complete answers to a national survey on risk and protective factors among adolescents. RESULTS: Over 80% of the adolescents who used alcohol and cigarettes were between 14 and 17 years old. The percentage of participants with antisocial behaviors was significantly higher among users of marijuana, cocaine, or crack than among adolescents who were not drug users. CONCLUSIONS: Prevention programs aimed at reducing substance use might help to decrease antisocial behaviors.